The Value of Efficiency in Photovoltaics - Peters, Ian Marius; Gallegos, Carlos David Rodriguez; Sofia, Sarah Elizabeth; Buonassisi, Tonio (Joule, 2019)
Herein, we introduce the value of efficiency (VOE)—a metric defining the allowable cost for innovation by analyzing the co-dependence of levelized cost of electricity (LCOE) on manufacturing cost and efficiency. Historically, VOE values have dropped rapidly and will further, yet slower, decline in the future. Additionally, VOE values for residential and utility installations converge at different levels, indicating a stronger diversification of these market segments. Similarly, local differences in VOE suggest a regional market diversification. Advanced concepts like n-type monocrystalline PERC silicon solar cells could be economically preferable to multicrystalline silicon solar cells in some countries but may fare worse in others, including China and India. Extending the analysis to tandem photovoltaics, we confirm its potential to improve LCOEs for residential applications but foresee challenges for utility markets. Finally, we explore detrimental impacts of degradation and show that competing for lower LCOEs demands matching degradation rates of established technologies. What is the value of increasing the efficiency of a solar cell? In this paper, we introduce the value of efficiency (VOE), a metric that determines the maximum allowable cost for an innovation to improve the levelized cost of electricity (LCOE). We then use this metric to analyze trends. Looking at historical data, we find that the VOE has declined rapidly in the past. Looking forward we still project a reduction but at a much-reduced pace. In addition, we observed that different markets converge at different values, indicating a technology diversification to better address different needs. One example is tandem solar cells, a high-efficiency photovoltaic (PV) concept that could help to provide electricity cheaper to homes in the future. We also observe a variation depending on location, indicating that different technologies could flourish regionally. Finally, we highlight the vital need for new PV technologies, like perovskites, to match leading technologies degradation rates. Here, we introduce the value of efficiency (VOE), a metric that determines the maximum allowable cost for an innovation to improve the levelized cost of electricity. We use this metric to analyze historic, regional, and technological trends. We find indications for a stronger regional and sectoral market diversification. One example is tandem solar cells that could help to reduce electricity costs in US residential installations. We highlight the need for new PV technologies, like perovskites, to match leading technology degradation rates.
CRIS-Team Scopus Importer:2022-06-05
Keywords: cost modeling; degradation; efficiency; LCOE; levelized cost of electricity; power conversion efficiency; stability